Composición florística de la regeneración natural de un bosque muy húmedo premontano en Poás, Costa Rica - Chinchilla Alvarado, Isler Fabián (2023)
Introduction: Natural restoration is a low cost and nature-based way to restore part of habitats degraded by deforestation. Objective: To document the floristic composition of a regenerating vegetation fragment of very wet premontane forest. Methods: We did a floristic inventory in 5,59ha through exhaustive walks. Results: We documented 74 families, 144 genera and 170 native species, and 15 families, 21 genera and 22 exotic species, and one hybrid. The families with the highest genera and species riches were Asteraceae, Fabaceae, Solanaceae, Rubiaceae, Euphorbiaceae, Polypodiaceae, Lauraceae, and Pteridaceae. The genera with the highest species richness were Solanum, Pleopeltis, Pteris, Croton, and Piper. We identified two endemic species, Costus montanus and Sechium tacaco. 95% of the species are terrestrial, 4% facultative epiphytes, and 1% holoepiphytes; 30% trees, 29% shrubs, 27% herbs, 9% lianas, and 5% dwarf shrub. About 64% are strictly heliophytes, and 36% of the species may tolerate shade. 148 species have at least one vernacular name. Conclusion: It is relevant to conserve this forest fragment, which is in an early state of regeneration, because its species composition typical of the premontane forests of the Costa Rican Central Valley.